Places of Engagement - van der Vaart, Rob (Amsterdam University Press, 2018)
In his book 'Higher Education in 2040 - A Global Approach' (2017) Bert van der Zwaan developed a thought-provoking vision of the university of the future, based on a thorough discussion of current trends and on a large number of conversations with leaders in higher education worldwide.